Effect of using Imported and Local Premixes on some Blood Parameters of Broiler (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This study had been conducted to investigate the effect of using premix that been locally mixed by different concentrations (Low , Standard and high) of excellent quality (used in starter and grower rations) and normal which is used in the finisher as alternative for foreign premix (provimi , excellent and normal) with comparison of their effect on some blood parameters of broilers.Total number of 120, one day old broiler chicks , Ross 308 were allotted randomly on 4 equal treatments , each treatment included 30 chicks and each treatment included 2 replicates (15 chick/ replicate). Chicks fed on rations according to ages of chicks (starter, grower and finisher) in which 2.5 % of one premix added in the experiment which were as follow :     Treatment 1 (T1) in which the foreign premix was mixed as an imported one, provimi. Meanwhile, the other treatments T2 , T3 and T4 in which the local premix was mixed by 3 concentrations (low, standard and high) respectively.    Mixing and preparation of rations was done in Al – Ghadder laboratory and factory in Al – Mahweel/ Babylon by depending on Best mix program, 2018 according to birds requirement, Ross 308 by a special manual 2014.Blood samples were collected from birds at 28 and 33 days in all treatments.        Results revealed significant variations (P